The Use of Modern Laboratory Methods for the Diagnosis of Tuberculosis in the Samarkand Regional Tuberculosis Dispensary (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In order to study modern laboratory methods for the diagnosis of tuberculosis in the Samarkand Regional tuberculosis dispensary, and their impact on intensive epidemiological indicators, existing laboratory methods and new innovative methods for the diagnosis of tuberculosis were analyzed. The use of high-tech laboratory methods for the diagnosis of tuberculosis based on PCR has allowed reducing morbidity and mortality from tuberculosis and improving the quality of life of patients.